Customer service in some local garment retail stores - Cardeño, Celeste C.; Dizon, Angelita Mendoza (1998.)
Millions can be earned if the key to customer needs and wants can be found. Customer service can help locate this key. Not only will it make the store profitable, it will also improve customer satisfaction, customer loyalty, and competitiveness. The general objective of the study is to determine which features of customer service are in demand as perceived by the respondents and which features are being offered by some garment retail stores. Specifically, the study attempts to (1) determine how important local customer service is with regard to the respondents' buying decision; (2) define customer service in terms of the respondents' needs and wants; find out which garment retail stores provide customer service, (4) determine which features of customer service do these garment retail stores prioritize; and (5) determine how to incorporate customer service into the store. One hundred college students from the University of the Philippines, Diliman, were surveyed. But first, they had to satisfy two requirements, namely, (1) their age should range from 18 - 23, and (2) they had to be residents of the campus' dormitories (excluding Sanggumay, Ipil-Ipil, Kalayaan, and the International Center.) Ten local garment retail stores at Shoe Mart North EDSA that the respondents consider to provide customer service also answered the researcher's questionnaire. To avoid being biased, the researcher also filled out questionnaires corresponding to her ratings for each particular garment retail store. Factor Analysis was applied to the data in order to determine which features of customer service the respondents and garment retail stores consider to be important. For the respondents, the analysis resulted in nine factors. However, for the garment retail stores, six factors were extracted. Table 8 lists the results of the Factor Analysis for both the respondents and the garment retail stores. Based on the results, the researcher was able to develop three aspects that garment retail stores must undergo before customer service can be internalized. These three aspects are (1) an internal review is essential; (2) total quality management and a total quality culture have to be targeted; (3) a store manual will have to be developed. The researcher presents the key to customer needs and wants. Unlocking the door is up to the garment retail stores. These needs and wants would have to be adopted and incorporated. The store's culture can undergo a roundabout change due to the new factors. But the store will also stand to gain a lot financially. Indeed, a smile can do wonders towards winning over a customer and conquering a scale.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing trade -- Customer service; Stores, Retail -- Customer service